Geomagnetic Deviation of Relativistic Electron Beams Producing Terrestrial Gamma Ray Flashes. Issue 9 (1st September 2020) - Celestin, Sebastien; Berge, Nini L.; Mailyan, Bagrat G.; Briggs, Michael S.
Abstract: In this work, we investigate the effect of the geomagnetic field on terrestrial gamma ray flashes (TGFs). Although this effect should be relatively weak for a single event, for example compared to the effect of the electric field orientation in the source region, it must be systematically present. Indeed, we show that a statistically significant excess of TGFs is detected to the east of their presumed lightning source by Fermi‐Gamma‐ray Burst Monitor (GBM). The corresponding eastward deviation is found to be likely greater than 0.1° in longitude, which is consistent with the expected effect of the geomagnetic field on relativistic runaway electron beams producing TGFs. Using analytical and numerical means, we show that the geomagnetic deviation can be used to estimate the magnitude of the electric field in TGF source regions. The electric field magnitudes we obtain are consistent with those necessary to drive relativistic runaway electron avalanches (RREAs). Key Points: Statistically significant excess of TGFs is detected to the east of their presumed sources by Fermi This is consistent with the expected geomagnetic field effect on relativistic runaway electron beams The discovered excess can be used to estimate the E‐ field in TGF source regions, which is found close to or larger than the RREA threshold